2021
DOI: 10.1016/j.heliyon.2021.e07223
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stress and associated factors among healthcare workers in Western Ghana

Abstract: Healthcare professionals are the most vulnerable to stress among all occupational groups due to the nature of their work environment. The aim of this study is to determine the level of stress and associated factors among healthcare workers in Western Ghana. The study employed a cross-sectional design with self-administered questionnaires. The results show that 69.5% of the respondents were stressed. Prevalence of stress was higher among female respondents than males. We found that 40.4 % of respondents intend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…The School of Public Health (SPH), School of Nursing and Midwifery (SONAM), and School of Medicine (SOM) are the project participating schools out of the six schools in UHAS. To understand the health needs of communities in Ghana, a community health needs assessment survey was conducted under the project [18] from 13th October 2018 to 8th February 2019 in the Volta Region.…”
Section: The Uhas-yonsei Partnership Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…The School of Public Health (SPH), School of Nursing and Midwifery (SONAM), and School of Medicine (SOM) are the project participating schools out of the six schools in UHAS. To understand the health needs of communities in Ghana, a community health needs assessment survey was conducted under the project [18] from 13th October 2018 to 8th February 2019 in the Volta Region.…”
Section: The Uhas-yonsei Partnership Projectmentioning
confidence: 99%
“…Other factors have been identified to influence psychological distress in Ghana and other countries in the sub-region. For instance, among healthcare workers in Western Ghana, age, educational background, marital status, and workload were reported to account for level of stress [18]. Additionally, age, sex, and social support were predictors of depression, anxiety and stress among people living with HIV/AIDS in Ghana [19], occupational stress also predicted depression among Ghanaian telecommunication workers [20], and sex, non-prescription drug use, caffeine consumption, and job prospects have significant impact on depression, anxiety, and stress among waiters in Ghana [21].…”
Section: Introductionmentioning
confidence: 99%
“…Further, counseling centers within healthcare facilities staffed with qualified psychologists has been shown to minimize occupational stress. 56,57 The frequent exposure of maternity providers to adverse events necessitates the availability of mental health support that is accessible and responsive. Of note, only 13% of providers in our study reported ever participating in a stress management training, 27 while only a few providers reported physical exercise, meditation, taking deep breaths or other coping mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals, especially those who acted as frontline workers during the COVID-19 pandemic, were highly vulnerable to stress among all occupational groups due to the nature of their work environment [ 1 , 2 , 3 ]. The level of stress among healthcare professionals was intensified with increasing rates of coronavirus infection and fatality leading to mental health vulnerabilities [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, healthcare professionals experienced heightened stress levels from the onset of the COVID-19 epidemic as frontline workers due to a dramatic shift in the regular ways of living and job routines in Ghana [ 54 , 55 , 56 ]. The lack of preparedness, inadequate working conditions, low healthcare worker: patient ratios (i.e., staff shortages), lack of personal protective equipment, limited testing capacity, lack of training and excessive workloads further exacerbated healthcare professionals’ stressful experiences [ 2 , 52 , 53 , 54 , 55 , 56 ]. The overall aim of this research, therefore, was to assess the validity and reliability of the cultural mix inventory for stressful situations among healthcare professionals in Ghana.…”
Section: Introductionmentioning
confidence: 99%